Analyzing Energy Materials by Cryogenic Electron Microscopy. Issue 24 (6th April 2020) - Ren, Xiao‐Chuan; Zhang, Xue‐Qiang; Xu, Rui; Huang, Jia‐Qi; Zhang, Qiang
Abstract: Safe and high‐energy‐density rechargeable batteries are increasingly indispensable in the pursuit of a wireless and fossil‐free society. Advancements in present battery technologies and the investigation of next‐generation batteries highly depend on the ever‐deepening fundamental understanding and the rational designs of working electrodes, electrolytes, and interfaces. However, accurately analyzing energy materials and interfaces is severely hindered by their intrinsic limitations of air and electron‐beam sensitivity, which restrains the research of energy materials in a low‐efficiency trial‐and‐error paradigm. The emergence of cryogenic electron microscopy (cryo‐EM) has enabled the nondestructive characterization of air‐ and electron‐beam sensitive energy materials in the microscale and nanoscale, and even at atomic resolutions, affording closer insights into the primary chemistry and physics of working batteries. Herein, the development of cryo‐EM and the applications in detecting energy materials are reviewed and analyzed from its overwhelming advantages in disclosing the underlying mystery of energy materials. Critical sample preparation methods as the precondition for cryo‐EM are compared, which strongly affect the characterization accuracy. Furthermore, new developments in the analysis of energy materials, especially bulk electrodes and interfaces in lithium metal batteries, are presented according to different functions of cryo‐EM. Finally, future directions of cryo‐EM for analyzing energy materials are prospected. Abstract : Cryogenic electron microscopy is employed in analyzing energy materials. New insights into the relationship between the action of a battery and the electrode, electrolyte, and interface chemistries are presented. This affords new perspectives for battery studies and guides the rational design of energy materials for a sustainable society.